2016
DOI: 10.1095/biolreprod.115.133454
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral Vector-Mediated Complementation Restored Fetal Viability but Not Placental Hyperplasia in Plac1-Deficient Mice1

Abstract: The X-linked Plac1 gene is maternally expressed in trophoblast cells during placentation, and its disruption causes placental hyperplasia and intrauterine growth restriction. In contrast, Plac1 is also reported to be one of the upregulated genes in the hyperplastic placenta generated by nuclear transfer. However, the effect of overexpressed Plac1 on placental formation and function remained unaddressed. We complemented the Plac1 knockout placental dysfunction by lentiviral vector-mediated, placenta-specific Pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In addition to the PAPPA biomarkers, the expression analysis of the novel X-linked gene PLAC-1 in FGR and normal pregnancies revealed marked differences between the two groups. Disruption of PLAC-1 can cause hyperplasia and FGR, whereas PLAC-1 is also reported to be one of the upregulated genes in the hyperplastic placenta generated by nuclear transfer ( 23 ). Although the association of PLAC-1 with the development of FGR during pregnancy has not been examined to date, previous studies demonstrated elevated levels of circulating PLAC-1 mRNA in preeclampsia that were directly related to the disease severity ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the PAPPA biomarkers, the expression analysis of the novel X-linked gene PLAC-1 in FGR and normal pregnancies revealed marked differences between the two groups. Disruption of PLAC-1 can cause hyperplasia and FGR, whereas PLAC-1 is also reported to be one of the upregulated genes in the hyperplastic placenta generated by nuclear transfer ( 23 ). Although the association of PLAC-1 with the development of FGR during pregnancy has not been examined to date, previous studies demonstrated elevated levels of circulating PLAC-1 mRNA in preeclampsia that were directly related to the disease severity ( 24 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Then, the Plac1 expression level decreased and its distribution became restricted. Plac1 knockout in the placenta was found to be attributed to the abnormal structure of spongiotrophoblasts, and knockout of Plac1 in the embryo has been shown to induce hydrocephalus [11], which can be rescued by Plac1 overexpression [26]. Furthermore, the possible function of Plac1 in the chorioallantois, umbilical cord, and uterus during pregnancy deserves our attention because its abundance and lasting expression in the chorioallantois, umbilical cord, as well as the uterine epithelium from 13.5 dpc was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Immunostaining was performed as described previously [ 42 , 43 ]. Briefly, all samples were mounted on glass slides and dried.…”
Section: Methodsmentioning
confidence: 99%